The early swimming behaviour hawksbill (erectmochelys imbricata) hatchlings - Chung, Fung Chen (Universiti Malaysia Sarawak, (UNIMAS), 2001)
Sea turtle hatchlings generally emerge from their nests and crawl rapidly to the sea. They then migrate offshore following a number of physical cues and natural physiological important mechanism for dispersal and predator avoidance during the first few days at sea.